Infant Death and the Archaeology of Grief. Issue 2 (23rd April 2015) - Cannon, Aubrey; Cook, Katherine
Abstract : To build a theoretical and empirical foundation for interpretation of the absence, segregation or simplicity of infant burials in archaeological contexts, we review social theories of emotion, inter-disciplinary views on the relationship between mortality rates and emotional investment, and archaeological interpretations of infant burial patterns. The results indicate a lack of explicit theory in most archaeological accounts and a general lack of consideration for individual variation and the process of change in mortuary practice. We outline the tenets of Bowlby's attachment theory and Stroebe and Schut's dual process model of bereavement to account theoretically for pattern, variation and change in modes of infant burial. We illustrate the value of this psychology-based perspective in an analysis of Victorian gravestone commemorations of infant burials in 35 villages in rural south Cambridgeshire, England, where individual and class-based variation, relative to falling mortality rates, is best explained as a function of coping strategies and contextually based social constraint on the overt representation of grief and loss.